Performance art in Eastern Europe since 1960 - Bryzgel, Amy (Rethinking art's histories., 2017)
This volume presents the first comprehensive academic study of the history and development of performance art in the former communist countries of Central, Eastern and South Eastern Europe since the 1960s. Covering 21 countries and more than 250 artists, this text demonstrates the manner in which performance art in the region developed concurrently with the genre in the West, highlighting the unique contributions of Eastern European artists. The discussions are based on primary source material-interviews with the artists themselves. It offers a comparative study of the genre of performance art in countries and cities across the region, examining the manner in which artists addressed issues such as the body, gender, politics and identity, and institutional critique.